Simventure: Utilizing first person player technology for career guidance in high schools - Norazri, Nurul Nadia; Mustafa Albakri, Ikmal Faiq Albakri; Mokhtar, Mohd Khalid; Mohamed, Farhan; Chan, Vei Siang; Nor'a, Muhammad Nur Affendy (2024)
The increasing trend of high school kids aspiring to become internet influencers or depending solely on freelance jobs, while ignoring their studies, motivated this study. This project seeks to enhance students’ awareness of their future by introducing Simventure. Simventure is an interactive simulation that has AI-driven Non-Playable Characters who provide assistance on post-graduation options and career planning, enabling students to investigate diverse career trajectories through a first-person perspective. While exploring career guidance and interactive learning, Simventure also reflect the reality in the career world such as becoming pilot and marine biologist. Simventure follows the ADDIE methodology (Analysis, Design, Development, Implementation, and Evaluation) as the foundation of the project. It explores the development of Simventure, covering asset development and the integration of AI into NPCs within the simulation. The simulations were afterwards evaluated through both quantitative and qualitative methods, engaging high school students and expert specialists, by employing the System Usability Scale (SUS) and expert testing to determine the usability and overall effectiveness of Simventure.